Peran Organisasi Internasional dalam Penegakan Hukum Lingkungan Global melalui Analisis Kebijakan Kualitatif - Mia Santoso (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The increasing fragmentation of global environmental governance has undermined the effectiveness of international environmental law enforcement. Despite the proliferation of multilateral environmental agreements, compliance among member states has declined, raising concerns about institutional coordination and accountability. This study aims to analyze the effectiveness of international environmental law by assessing institutional synergy among major global organizations, including UNEP, GEF, and the WTO. Using a mixed normative-empirical legal method, the research evaluates 96 policy documents and institutional reports and conducts interviews with 14 international law experts from 2015 to 2023. The findings reveal a significant correlation of 0.82 between state participation and compliance, demonstrating that collective engagement improves enforcement consistency. However, the overall compliance rate has dropped to 63 percent in the last five years, indicating persistent institutional fragmentation. The correlation between financial assistance and compliance (r = 0.57) suggests that funding alone is insufficient without transparent governance structures. Comparative results also show that organizations with higher levels of policy harmonization exhibit 25 percent greater implementation effectiveness than those operating under fragmented systems. The study concludes that legal coherence, institutional capacity, and collaborative governance are critical determinants of the effectiveness of environmental law. The novelty of this research lies in introducing the concept of institutional synergy as a measurable indicator for assessing the integration and efficiency of international environmental regimes, offering new insights into the intersection of law, policy, and global sustainability governance